(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Anti-inflammatory drugs are one of the main tools for the treatment of acute and chronic pain in a wide range of diseases and pathological conditions. The use of anti-inflammatory drugs is an integral part of the practice of therapists, rheumatologists, neurologists, anesthesiologists, surgeons, traumatologists, gynecologists, etc.